ZOOBENTOS COMMUNITY STRUCTURE IN THE MANGROVE ECOSYSTEM OF THE MENGKAPAN VILLAGE, SUNGAI APIT DISTRICK, SIAK REGENCY - Irwanna, Muhammad Robby; Adriman, Adriman; Sumiarsih, Eni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Zoobenthos can be used as bioindicator of water quality. A study aims to understand the structure of zoobenthos community in mangrove area of the Mengkapan village has been conducted in November - Desember 2018. Zoobenthos were collected manually, namely S1 (around the oil pipe), S2 (residential area) and S3 (natural area). Water quality parameters measured measured were temperature, pH, salinity, and sediment fraction and organic matterials content in the sediment. There were 7 types of zoobenthos presence and they were belonged to 3 classes, namely gastropoda (4 species), malacostraca (1 species), and polychaeta (2 species). zoobenthos abundance ranges from 72 - 83organisms / m2. The species diversity index (H ') ranged from 2.551 - 2.617, the dominance index (C) ranges from 0,177 – 1,198 and uniformity index (E) ranged from 0.909 - 0.932. Water quality parameter values were as follows: temperatures 25-28 ° C, water pH 6-7, soil pH ranges from 6-7, salinity 22-260/oo. The sediment was sandy mudwith organic materials 32,14% - 35,51%. Key words:Coastal Area, Polychaeta, Gastropoda, Malacostraca